2014
DOI: 10.1002/tia2.20004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Promise: A Learning-Focused Syllabus Rubric

Abstract: To enrich the resources for measuring the impact of educational development work, we have created a rubric to assess the degree to which a syllabus achieves a learning orientation. The rubric provides qualitative descriptions of components that distinguish learning‐focused syllabi and uses a quantitative scoring system that places syllabi on a spectrum from content‐focused to learning‐focused. It is flexible enough to accommodate a diverse range of levels, disciplines, institutions, and learning environments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 15 publications
0
39
1
5
Order By: Relevance
“…We drew from the available literature on assignment design, built upon Winkelmes et al's transparency model and important research findings, and considered the value‐expectancy theory of achievement motivation to create a first draft. We modeled the specific structure and scoring system of the assignment rubric on the valid and reliable learning‐focused syllabus rubric of Palmer et al ().…”
Section: The Design Processmentioning
confidence: 99%
See 1 more Smart Citation
“…We drew from the available literature on assignment design, built upon Winkelmes et al's transparency model and important research findings, and considered the value‐expectancy theory of achievement motivation to create a first draft. We modeled the specific structure and scoring system of the assignment rubric on the valid and reliable learning‐focused syllabus rubric of Palmer et al ().…”
Section: The Design Processmentioning
confidence: 99%
“…Researchers have observed similar benefits when the basic principles of transparency are applied to other teaching documents. For example, Palmer, Wheeler, and Aneece () showed that when instructors create more transparent, learning‐focused syllabi (Palmer, Bach, & Streifer, )—those characterized by clearly stated learning goals and objectives, robust assessment and activity descriptions, detailed course schedules, and a focus on student success—students have more positive perceptions of the document, the course, and the instructor. Specifically, students viewed a learning‐focused syllabus as a useful, organizing document; the associated course as an interesting, relevant, and rigorous learning experience; and the instructor as a caring and supportive individual integral to their learning process.…”
mentioning
confidence: 99%
“…Syllabi have been seen as one of the ways in which academic programs are robustly taught (Palmer et al 2014). Faculty members use a class syllabus as basis for learning (Heffernan 2001;Parkes and Harris 2002) and competence (Petrovici and Masari 2014).…”
Section: Teaching Development Communicationmentioning
confidence: 99%
“…Palmer, Bach and Streifer (2014) argue that a properly designed curriculum, as seen in the curriculum's set of learning-centred syllabi, accounts for how much content is absorbed by the students. Literature has also argued that significant learning occurs when teachers and academic administrators see the syllabi as a kit for engaging students in cognitive, affective and self-directed learning (Fink 2013;Anderson et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors should have stressed the importance of sound course design where goals, assessment and activities are aligned and integrated (see, e.g. Fink, 2003;Palmer, Bach, & Streifer, 2014;Wiggins & McTighe, 2005). Contemplative practiceslike any other learning activitiesneed to be driven by and supportive of the particular goals and objectives for that course.…”
mentioning
confidence: 99%